HISTOLOGICAL AND HISTOCHEMICAL STUDIES OF THE NEUROSECRETORY CELLS OF ABEDUS OVATUS (STAL) (INSECTA : BELOSTOMATIDAE) - LALITHA, T. G.; SHYAMASUNDARI, K.; RAO, HANUMANTHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Four types of neurosecretory cells (NSCs), designated as A,B,C and D cells were observed in the brain and ventral ganglia of Abedus ovatus. 'A' cells were encountered only in pars intercerebralis while B, C and D were distributed in subOesophageal and the fused thoracico and abdominal ganglia. The histochemical observations of the neurosecertory material (NSM) revealed that it is a protein, rich in disulfides, sulfhydrils and glycoproteins associated with phospholipids.